THE INFLUENCE OF TEACHING MATERIALS DEVELOPMENT ON STUDENT UNDERSTANDING IN CLASS VII ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT IT MIDDLE SCHOOL. AN-NAFIS TELUK MENGKUDU DISTRICT SERDANG BEDAGAI DISTRICT - Chairuddin Siregar; Irdian Ningsih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This research uses a quantitative approach, where the symptoms are measured using numbers. The results of the research in this thesis, There is a significant positive relationship between the development of teaching materials on students' understanding of class VII Islamic Education subjects. This is evidenced by the results obtained, namely by using the product moment correlation formula, the correlation index value is obtained of 0.808 which ranges from 0.70 to 0.90, this means that there is a significant correlation between variable X and variable Y, namely a strong or high correlation. Then by examining the table of the value of "r" product moment, it turns out that with a df of 50 at the 5% significance level, the "r" table is 0.297, then at the 1% significance level the value is 0.361 . If we look at the number " Barriers to understanding students in class VII Islamic Education subjects are not entirely due to the development of teaching materials, but it is likely that these teaching materials have indeed become one of the factors that can affect the inhibition of student understanding. This is evidenced by 100% of the development of teaching materials in accordance with KI and KD. Barriers to understanding students in class VII Islamic Education subjects are not entirely due to the development of teaching materials, but it is likely that these teaching materials have indeed become one of the factors that can affect the inhibition of student understanding. This is evidenced by 100% of the development of teaching materials in accordance with KI and KD.